Food Budget of Inmates and Their Body Mass Index - Pallega, Rowell B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This study aimed to evaluate the food budget allowance of inmates in Dapitan and Dipolog City jail and determine the inmates body mass index as one of the indicators in assessing the nutrition of person whether he/she is malnourished or not. The study employed a mix of quantitative and qualitative approaches in carrying out the results of the study. Quantitative method was used to describe the inmate’s profile as to age, gender, number of years in jail, types of food served and body mass index. While qualitative method was used to determine the budget allocation of inmates and medical records of inmates. An information sheet was created and distributed to the inmates who were the primary respondents in order to gather quantitative data. In addition, unstructured interview was also conducted to the warden during site visit. Random sampling method was used. Descriptive statistics were used in presenting, analyzing and interpreting the data of the study. Most of the inmates incarcerated are within the age ranging from 42-51 years old, while most of the inmates are incarcerated for a period ranging from 2 to 4 years. There are very few inmates with medical history like ulcer, diabetes, mayoma and high blood. Beef or pork tinola with sayote and rice is the commonly meals serve to the inmates. Majority of the inmates are within normal weight. Monitoring of those inmates with medical history to prevent from any possible complications.